The Influence of Task Complexity, Audit Expertise, and Self-Efficacy on Audit Judgment - Kamal, Muhammad Hardi Kasriadi; Akob, Muh.; Lalo, Annas (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2025)
Purpose – The purpose of this study was to examine and analyze the effect of task complexity, audit expertise, and self efficacy on audit judgment. Design/methodology/approach – The population in this study were auditors who worked at public accounting firms (KAP) in South Sulawesi, while the sample of this study was 63 auditors who worked at public accounting firms in Sulawesi. This research uses multiple regression analysis method. Findings – The results of this study indicate that the complexity of the task has a negative and significant influence on audit judgment. The auditor's expertise has a positive and significant influence on audit judgment. Then seen from self efficacy has a positive and significant influence on audit judgment. The implication of the theory in this study can show from the theory that has been done, namely the change in the perception of understanding of each individual after having experience and knowledge in him. Practical implications in this research are expected to be beneficial for the Public Accounting Firm, namely regarding the factors that affect audit judgment including: task complexity, audit expertise and self efficacy. Originality – This research investigates the effect of task complexity, audit expertise, and self efficacy on audit judgment. Keywords: Task Complexity, Audit Expertise, Self efficacy, and Audit judgment Paper Type Research Result